Risk Factors for Loss of Lung Sliding in a Medical Intensive Care Population With Acute Respiratory Failure. Issue 2 (April 2019) - Mallow, Christopher; Isakow, Warren
Abstract : Background: Point of care bedside ultrasound is widely utilized as a rapid technique to evaluate patients with acute pulmonary emergencies, including acute pneumothorax. The presence of a pneumothorax is a known cause of loss of lung sliding by ultrasound examination, but no other risk factors have been clearly identified. We attempted to identify demographic and patient characteristics that are risk factors for loss of ultrasonographic lung sliding in the absence of a pneumothorax. Methods: Data were collected on 159 patients admitted to the medical intensive care unit with acute respiratory failure, undergoing routine admission lung ultrasound. The lung ultrasound examination consisted of 3 views of each hemithorax using a phased array abdominal probe. Results: There were 4 confirmed pneumothoraces out of 20 patients with loss of lung sliding at ≥1 ultrasound interrogation points on either hemithorax. Hypercarbic respiratory failure [odds ratio (OR), 5.59] and low body mass index (OR, 0.88) were statistically significant risk factors for the loss of lung sliding in the absence of pneumothorax. There was a trend toward significance in patients with a known history of a decreased forced expiratory volume 1/forced vital capacity ratio (OR, 0.02), COPD/asthma exacerbation as the cause of their respiratory failure (OR, 4.52) and previous pneumothorax (OR, 11.53). Conclusion: Common diagnoses and comorbidities are associated with the loss of ultrasonographic lung sliding, in the absence of pneumothorax.